Electrostatic potential variation on the flux surface and its impact on impurity transport. (17th March 2017) - García-Regaña, J.M.; Beidler, C.D.; Kleiber, R.; Helander, P.; Mollén, A.; Alonso, J.A.; Landreman, M.; Maaßberg, H.; Smith, H.M.; Turkin, Y.; Velasco, J.L.
Abstract: The impurity transport in magnetically confined plasmas under some conditions finds neither quantitatively nor qualitatively a satisfactory theory-based explanation. This compromises the successful realization of thermo-nuclear fusion for energy production since impurity accumulation is known to be one of the causes that limits the plasma performance through radiative losses and plasma dilution. Under stellarator reactor-relevant conditions, accumulation is supported by the negative (inwards pointing) radial electric field which must arise to satisfy the ambipolarity constraint on the neoclassical particle fluxes. The high charge number of the impurities makes their transport particularly sensitive to the presence of electric fields and, consequently, the electrostatic potential variation on the flux surface, Φ 1, which conventional neoclassical theory usually neglects, may contribute to the theoretical interpretation of experimental results not yet fully understood, e.g. Ida et al (2009 Phys. Plasmas 16 056111 ) and Yoshinuma et al (2009 Nucl. Fusion 49 062002 ). In the present work we have considered different stellarator configurations and assessed the impact that Φ 1 has on the radial particle transport of selected impurities. The results for LHD show that Φ 1 can strongly modify this transport, resulting in large deviations of the level of inward impurity flux predicted by the standard neoclassical theory in most cases. In Wendelstein 7-X, on the contrary, Φ 1 is significantly smaller and, for the parameters considered, its effect only appreciable for impurities with high charge number. Finally, in TJ-II the potential variation leads to appreciable changes of the impurity radial flux, although not to the extent its large amplitude might lead one to think. The dependence on the chosen parameters and open questions for future developments are discussed.